Adhesion Testing of Direct-Write Printed Ink on Metallic Structural Components - Timothy L. Phero; Amey R. Khanolkar; James A. Smith; Bradley C. Benefiel; Shaun P. Evans; Michael D. McMurtrey; David Estrada; Brian J. Jaques (IEEE Open Journal of Instrumentation and Measurement)
The successful adoption of additive manufacturing for the rapid prototyping of direct-write printed electronics requires the establishment of quantifiable metrics. These metrics should directly interrogate the fabrication quality of the device during the manufacturing process. This implies that the characterization technique should be nondestructive. One measure of fabrication performance is the adhesion strength between the substrate and printed film interface, which is critical since the strength of this interface can dictate the accuracy and reliability of the printed device. In this work, a noncontact laser-induced spallation technique has been used to estimate the adhesion of silver-printed films on aluminum alloy substrates. The laser-based method was compared to a standardized pull-off adhesion test, which provided baseline measurements of adhesion strength. These adhesion measurement techniques were compared against the sintering condition-dependent microstructure of the additive manufacturing films. The porous structure of the printed thin film was found to be an important factor that impacted adhesion tests that utilize adhesives (i.e., glue and resins) due to an enhanced interlocking to the adherend surface. Due to its noncontact nature and insensitivity to thin samples/films, laser spallation was found to be a more reliable indication of process parameter change. The methods and results described in this work support the establishment of process control steps that are necessary for quickly verifying the reliability of printed devices prior to their deployment in critical experiments.